2011
DOI: 10.1260/2040-2317.2.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Test Results and Model for the Residual Compressive Strength of Concrete After a Fire

Abstract: An investigation into temperature induced degradation of the compressive strength of concrete including that under cooling phase is carried out. The paper gathers and reviews a considerable amount of test data, considering the influence of different test parameters such as initial compressive strength, aggregate type, cooling regime and specimen shape. It is found that the compressive strength of concrete at high temperature is in accordance with the model proposed in the Eurocodes for calcareous concrete. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…Table 1 gives peak temperatures measured in several locations for each column at any point during the heating and cooling phases of the fire tests. Note that temperatures in the concrete tended to increase for a period during the cooling phase, as expected, due to the thermal wave continuing to move through the cross sections [18]. At the column centreline, for instance, peak temperatures continued to increase as much as 90°C twenty-five minutes into the cooling phase for unprotected columns, whereas for protected columns peak temperatures during cooling were up to 180°C greater than at the end of the heating phase and in some cases occurred more than 100 min into cooling.…”
Section: Recorded Temperaturessupporting
confidence: 61%
See 1 more Smart Citation
“…Table 1 gives peak temperatures measured in several locations for each column at any point during the heating and cooling phases of the fire tests. Note that temperatures in the concrete tended to increase for a period during the cooling phase, as expected, due to the thermal wave continuing to move through the cross sections [18]. At the column centreline, for instance, peak temperatures continued to increase as much as 90°C twenty-five minutes into the cooling phase for unprotected columns, whereas for protected columns peak temperatures during cooling were up to 180°C greater than at the end of the heating phase and in some cases occurred more than 100 min into cooling.…”
Section: Recorded Temperaturessupporting
confidence: 61%
“…up to 80-90% reduction) the concrete core's ability to carry load [17,19], and in these columns it is expected that the majority of the residual load carrying capacity would be due to the steel tube, which can be expected to regain as much as 65% of its ambient temperature strength after cooling from temperatures as high as 1000°C (Fig. 1c) [18,20]. Fig.…”
Section: Recorded Temperaturesmentioning
confidence: 99%
“…The post-fire reduction in the mechanical properties of concrete represents an important research topic since most of the research projects investigating concrete properties in fire conditions have mainly focused on testing the hot and residual properties [1]- [3]. The hot and residual mechanical properties, such as compressive strength, are regularly used as a representative parameter for modelling concrete behaviour during the heating and cooling phases of a fire.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30] have been conducted on the effect of elevated temperature on concrete strength which showed that that the general trend of the compressive strength decreases as the temperature is increased. For this purpose different scenarios were addressed with the specimens being tested using one or more of the following three combinations of heating and loading: (a) stressed during heating and tested at high temperature, (b) unstressed during heating and tested at high temperature, and (c) unstressed during heating and tested after cooling (i.e.…”
Section: Introductionmentioning
confidence: 99%